Association between surgery treatment delays and survival outcomes in patients with esophageal cancer in Hebei, China - Cui, Xing; Shi, Chunxiao; Chen, Xin; Zhao, Qi; Zhao, Jidong (Frontiers in Oncology, 2024)
IntroductionThe delays in cancer therapies have the potential to impact disease progression by allowing the unchecked growth and spread of cancer cells. However, the understanding of the association between treatment waiting time and survival outcomes in patients with esophageal cancer (EC) is limited. This study aims to assess the impact of waiting time on survival outcomes among EC patients in Hebei province, which is recognized as one of the high-risk areas for EC in China.MethodsA total of 9,977 non-metastatic EC patients who underwent surgical treatment were identified between 2000 and 2020. The survival outcomes of overall survival (OS) and cancer-specific survival (CSS) were determined using the Kaplan-Meier methodology. Univariate and multivariate Cox regression analysis was employed to evaluate the impact of treatment delays on OS and CSS.ResultsThe average delay time for initiating EC surgical treatment after diagnosis was 1.31 months (95%CI=1.29–1.34). Patients with a long delay (≥ 3 months) in treatment, comprising 9977 EC patients, exhibited significantly lower rates of 3-, 5-, and 10-year OS and CSS compared to those without any delay in treatment initiation. A long delay in EC treatment independently associated with an elevated risk of all-cause and cancer-cause mortality among various patient subgroups, including males, older individuals, single individuals, low-income patients, residents of nonmetropolitan counties, as well as those diagnosed with poorly differentiated and stage IV EC.DiscussionThe long delay of treatment initiation impacts the outcomes of OS and CSS in EC patients. Optimizing treatment timing may enhance life expectancy for individuals diagnosed with EC.